Training in Making Digital Story Telling Learning Media for Paud Teachers in Jalaksana District - Nika Cahyati; Chitra Charisma Islami; Rita Kusumah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The purpose of implementing the community partnership program in the form of this training is to improve the competence of teachers in Indonesia to create, develop and implement learning media in the form of digital storytelling. This training was carried out for PAUD teachers in Jalaksana District, Kuningan Regency. The problem with learning partners is that teachers rarely use learning media when learning in class. This makes the motivation and achievement of students less increase. Even though it is known that the demands of the 2013 curriculum and the rapid pace of science and technology require creative teachers to use technology-based learning media. The potential for PAUD teachers in the Jalaksana sub-district is quite large and the presence of technological devices in schools is sufficient, but in terms of competence, it needs to be continuously improved. This is due to the absence of special training activities for the manufacture of technology-based learning media. The solution to these problems is the implementation of training in making digital storytelling learning videos. This training activity consists of stages, namely, field surveys, coordination with school principals and teachers, program socialization, program implementation and activity evaluation.